PSYCHOLOGICAL ISSUES OF THE FORMALIZATION OF VALUES IN REQUIREMENTS WITHIN A VALUE SYSTEM AND A MULTICULTURAL SYSTEM - Leyla, Baloglanova; Mahizar, Eyyubova; Rugayya, Aghayeva; Sariyya, Asadullayeva (Health and Society, 2026)
In this article, values in a multicultural environment are systematically analyzed in a broad sense and from various perspectives. Numerous theoretical approaches to this issue are grouped. It is also noted that the currently existing approaches to values lead to differences in their structure. In this context, the transformation of national-moral values among students divides young people into different camps. The main purpose of the study is to determine the formation of students’ value orientations, the changes that occur in them, and the role of socio-psychological factors in this process. According to the results of the experimental study, age is one of the main factors that directs the transformation of values. As age increases and the influence of the social environment grows, moral categories in the hierarchy of values are replaced by material categories. The study showed that for student youth in a multicultural environment, an adequate assessment of moral values directly depends on their intellectual level and worldview. It was found that high intelligence and a broad knowledge base in young people allow them to adapt to a new environment within cultural diversity, preserving their conservative status despite external pressures. In conclusion, it can be stated that to prevent the deformation of moral values, students’ self-awareness and understanding of their national identity, along with the development of their analytical thinking skills, play a leading role in regulating their behavior.